Impact of Selected Endocrine Dysfunctions on Physical Performance and Sports Outcomes: A Literature Review - Gawin, Konrad; Zawiślak, Wiktoria; Cisowski, Michał; Dąbrowska, Maria; Rychlica, Kacper; Cholewińska-Rychlica , Jolanta; Madura, Paulina; Mrozik-Gałecka, Daria (Quality in Sport, 2026)
Hormonal regulation is essential for maintaining physiological homeostasis and enabling adaptation to physical stress, making the endocrine system a key factor influencing athletic performance and training responses. Hormones such as thyroid hormones, cortisol, testosterone, and growth hormone regulate metabolism, cardiovascular function, muscle performance, and recovery. Disruptions in endocrine function—resulting from gland disorders or training-related factors such as low energy availability—may impair exercise capacity and adaptation to training. This narrative review summarizes recent literature on the relationship between selected endocrine disorders and sports performance, focusing on thyroid dysfunction, cortisol-related disorders, and pituitary abnormalities. Evidence suggests that thyroid disorders can affect cardiovascular efficiency, neuromuscular performance, and metabolism, while adrenal dysfunction may impair stress responses and exercise tolerance. Hypercortisolism and Cushing syndrome are associated with reduced aerobic capacity, muscle weakness, and sarcopenia, whereas pituitary dysfunction, including that related to traumatic brain injury or relative energy deficiency in sport, can disrupt multiple hormonal axes and influence physical capacity. Overall, endocrine disorders may significantly affect physical performance and athlete health. Early detection, regular hormonal monitoring, and individualized medical and training strategies are essential to support safe training and optimize performance outcomes.